2017
DOI: 10.1186/s12920-016-0242-1
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant women carrying microcephaly foetuses and Zika virus contain potentially pathogenic microbes and parasites in their amniotic fluid

Abstract: BackgroundMicrocephaly has become a major public health problem in Brazil. The total number of newborns with microcephaly was reported to be >4000 in June 2016. Studies suggest that Zika Virus is a major cause of new microcephaly cases in Brazil. Inside the uterus, the foetus is surrounded by the Amniotic Fluid, a proximal fluid that contains foetal and maternal cells as well as microorganisms and where Zika Virus was already found.Case presentationA previous study reported the presence of the Zika Virus in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Certain data support the notion that bacteria colonization in humans will begin in the gestation at the womb (Stinson et al, 2017 ). Consistently, several reports have detected the presence of bacterial DNA in the amniotic fluid, umbilical cord, placenta, meconium, and fetal membranes (Khan et al, 2016 ; Stinson et al, 2017 ; Tschoeke et al, 2017 ). This evidence is in contrast with the hypothesis of the sterile womb and that bacteria colonization in humans begins only at birth or at breastfeeding (Funkhouser and Bordenstein, 2013 ).…”
Section: The Microbiota Through Human Lifesupporting
confidence: 63%
“…Certain data support the notion that bacteria colonization in humans will begin in the gestation at the womb (Stinson et al, 2017 ). Consistently, several reports have detected the presence of bacterial DNA in the amniotic fluid, umbilical cord, placenta, meconium, and fetal membranes (Khan et al, 2016 ; Stinson et al, 2017 ; Tschoeke et al, 2017 ). This evidence is in contrast with the hypothesis of the sterile womb and that bacteria colonization in humans begins only at birth or at breastfeeding (Funkhouser and Bordenstein, 2013 ).…”
Section: The Microbiota Through Human Lifesupporting
confidence: 63%
“…In 2013, the virus spread to the Pacific and later to the Americas [3]. In that context, Brazil was one of the most affected countries with a drastic increase in microcephalic newborns (20-fold increase) in 2015 compared with previous years [4,5]. These findings caused an explosion in investigations about microcephaly reaching 1080 published articles in 2016 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In 2015, Brazil was the epicenter of ZIKV in the Latin American outbreak [3]. A year later, Brazil reported an increase of 20 times in the number of cases of microcephalic newborns, which raised suspicions of vertical transmission [4,5]. Different from other flaviviruses, several studies have demonstrated the ZIKV capacity to cross the placenta barrier and impair fetal neurogenesis, causing abnormal brain function [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%